BRS Araçari and BRS Biguatinga: Embrapa´s new habanero pepper cultivars - Ribeiro, Cláudia S.C.; Soares, Renato S. [UNESP]; de Carvalho, Sabrina I.C.; Nass, Luciano L.; Lopes, Carlos A.; Lima, Mirtes F.; Nagata, Alice K.I.; Reis, Ailton; Quezado-Duval, Alice M.; Pinheiro, Jadir B.; Maldonade, Iriani R.; Hanashiro, Marcelo M.; et al. (FapUNIFESP (SciELO), 2024)
Embrapa Vegetables´ Capsicum breeding program has contributed significantly with several nonpungent and pungent pepper cultivars and hybrids released to the Brazilian market, focusing mainly on disease resistance and superior industrial and nutritional quality of fruits. The habanero chile pepper cultivars BRS Araçari and BRS Biguatinga were developed by Embrapa´s breeding program to meet both the market for fresh fruit and processing agroindustry of mashes and sauces. ‘BRS Araçari’ pods are rectangle-shaped, turn from dark green to bright yellow when mature, and are 4.3 cm long by 4.2 cm wide and have 1.8 mm in wall thickness. Fruits have a pungency of circa 5,000 SHU (Scoville Heat Unit) and high vitamin C content (177.4 mg/100 g). ‘BRS Biguatinga’ pods are campanulate-shaped, the standard shape of habaneros, turn from light green to red when ripe, 6.6 cm long by 3.4 cm wide and 1.9 mm in wall thickness. Fruit pungency is circa 150,000 SHU and fruits have 149 mg/100 g fruit of vitamin C and 221 µg/g fruit of carotenoids. Both cultivars are resistant to important chile pepper diseases, present high yield, uniformity and fruit quality, and have been successfully cultivated in conventional and organic production systems in Brazil. ‘BRS Araçari’ and ‘BRS Biguatinga’ were registered and protected by the Brazilian Ministry of Agriculture and Livestock, and seeds of cultivar BRS Araçari are being marketed by Isla Sementes. ‘BRS Biguatinga’ basic seeds are being offered to the production sector through Public Call for Tenders for interest parties in becoming Embrapa’s partners for the production and sale of commercial seeds.
BRS Araçari e BRS Biguatinga: Novas cultivares de pimenta habanero da Embrapa Hortaliças
Keywords: capsaicinoids; Capsicum chinense; fresh market; processing; resistance